2007
DOI: 10.1111/j.1600-0765.2006.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A‐associated proteins from Porphyromonas gingivalis stimulate release of nitric oxide by inducing expression of inducible nitric oxide synthase

Abstract: The present study clearly shows that P. gingivalis lipid A-associated proteins fully induced inducible nitric oxide synthase expression and nitric oxide production in RAW264.7 cells in the absence of other stimuli. The ability of P. gingivalis lipid A-associated proteins to promote the production of nitric oxide may be important in the pathogenesis of inflammatory periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…However, the mechanisms by which these molecules mediate their pathogenic effects have not been fully delineated. Reports indicate that periodontopathic bacteria and bacterial components, including LPS, stimulate local gingival fibroblasts and inflammatory cells, including macrophages, to produce nitric oxide (2,7,12,17,41,46,61,66). In agreement with these findings, our data show for the first time that PDL cells also respond to an LPS challenge by producing increased levels of nitric oxide and iNOS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the mechanisms by which these molecules mediate their pathogenic effects have not been fully delineated. Reports indicate that periodontopathic bacteria and bacterial components, including LPS, stimulate local gingival fibroblasts and inflammatory cells, including macrophages, to produce nitric oxide (2,7,12,17,41,46,61,66). In agreement with these findings, our data show for the first time that PDL cells also respond to an LPS challenge by producing increased levels of nitric oxide and iNOS.…”
Section: Discussionsupporting
confidence: 81%
“…Due to its small size and neutral charge, it can diffuse freely through the cell membrane and act as a signaling and effector molecule. iNOS is typically not present in a cell but can be induced when cells are stimulated by bacterial endotoxins and proinflammatory cytokines (12). Once induced, iNOS can produce nearmicromolar amounts of nitric oxide for sustained periods of time, and this production is independent of calcium ions.…”
mentioning
confidence: 99%
“…The cells were distributed to the plates at a concentration of 1×10 6 cells/mL and incubated for more than 2 h to attach the cells onto the plates. LPS (1 μg/mL) was treated with β-glucan and incubated for 24 h (Choi et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…By using a 96 well plate, 100 μL of the Griess reagent (1% sulfanilamide, 0.1% naphthylethylene diamine dihydrochloride, and 2.5% phosphoric acid) (sigma), which was equivalent to the volume of the cell incubate supernatant, was mixed and reacted for 10 min to measure the absorbance at the wavelength of 540 nm using a Spectra Max 250 ELISA Reader (Molecular Devices, USA). The nitrite concentration was determined by using a standard curve that was produced by consecutively diluting NaNO 2 (sigma) with the incubate solution (Choi et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…The detection of high amounts of the NO precursors L-arginine and L-citrullin in inflamed gingival tissue in vivo (Matejka et al 1998), and iNOS expression in macrophages, lymphocytes and PMN neutrophils in experimentallyinduced periodontitis in rat (Lohinai et al 1998) as well as in macrophages, endothelial cells (Lappin et al 2000) and PMNs (Batista et al 2002) in human periodontitis suggests the production and participation of NO in PD. Attempting to throw light on the signaling mechanisms involved in induced NO production by a murine macrophage cell line, the study of Choi et al (2007) indicated that multiple signaling pathways, such as nuclear factor-jB, protein tyrosine kinase, protein kinase C, and MAPK cascades, are coordinated in NO production induced by P. gingivalis lipid A-associated protein.…”
Section: Introductionmentioning
confidence: 99%